Klasifikasi Tanah Di Lereng Selatan Gunung Burni Telong Kecamatan Bukit Kabupaten Bener Meriah Provinsi Aceh - Thasniema Putri; Purba Marpaung; Razali Razali (Jurnal Agroekoteknologi, 2015)
The research at south slope of mount Burni Telong is aimed to soil classification with theclassification system of Soil Taxonomy, 2014 into sub grup category which was conducted inFebruary – September 2014. Two selected pedons were observed at middle slop (Va.1.6.1t) andbottom slope (Va.1.4.1t). Soil samples were taken from each horizon for analysis bulk density, pH(H2O), pH (KCl), pH (NaF), Al, cation exchange capacity, base saturation, qrganic carbon,phosfat retention in Research and Technology Laboratory, Agricultural Faculty of North SumateraUniversity, Medan and analysis of soil texture, Al-oxalate extracted (Alo), Si-oxalate extracted(Sio), and Fe-oxalate extracted (Feo) in Soil Laboratory, Soil Research Institute, Bogor.The resultof this research is the classification in the middle slop soil (Va.1.6.1t) is Humic PsammenticDystrudepts, and on the bottom slope soil (Va.1.4.1t) is Typic Hapludands.Keywords: Mount Burni Telong, Soil Classification, Soil Taxonomy dd